Pengaruh Budaya VOC Menumbuhkan Korupsi di Kalangan Penguasa Indonesia di Era Kolonial - Amelia Claudia; Atha Prima Azaria; Ghina Annisa Nurshaliha; Intan Asri Hakim (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Indonesian history records the important role of the Vereenigde Oost-Indische Compagnie (VOC) in shaping culture and government systems. The VOC, a Dutch trading company, was dominant in the colonial era, controlling territory that is now part of Indonesia, Malaysia and Singapore. In its influence, the VOC not only brought Western culture but also expanded corrupt practices in Indonesia. This study uses qualitative research methods with a focus on literature study. Data was obtained through analysis of primary and secondary sources, as well as interviews with historians. This approach allows for an in-depth understanding of VOC culture and the impact of the corruption it initiated. Corruption started by the VOC is still a continuing problem in Indonesia because it has affected culture, social structure and government. Efforts to overcome this problem require hard and consistent work from the government and society. The VOC's influence not only introduced corruption during the colonial period, but also left a lasting legacy that influences Indonesia to this day. This corruption has become integrated into the culture and system of government, requiring continued efforts to overcome its impacts.